Effect of Protective Measures on the Risk of SARS-CoV-2 Infection among Eye Clinic Staff Members - Sanak, Frantisek; Faes, Livia; Eppenberger, Leila; Baenninger, Philipp; Kaufmann, Claude; Golla, Kathrin; Bachmann, Lucas; Buhl, Daniela; Schmid, Martin K.; Thiel, Michael (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Switzerland was strongly affected by the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that resulted in a nationwide lockdown in March 2020. Ophthalmologists were at most risk of contracting a SARS-CoV-2 infection due to their close working distance from patients. The aim of the study is to evaluate the overall effectiveness of protective measures on the risk of SARS-CoV-2 infection among employees in a large public eye hospital.Material and Methods After lifting the lockdown in April 2020, standard precaution measures were taken, such as no handshaking and the use of operating face masks and a protective plastic shield on slit lamps and diagnostic devices. Only patients with no signs of SARS-CoV-2 disease were seen during the study period. Specific anti-SARS-CoV-2 IgG antibody titers were measured in eye clinic employees at the end of April 2020 (1st test phase) and in January 2021 (2nd test phase). The prevalence of SARS-CoV-2 IgG antibody titers among employees with daily patient contact was compared to staff members with no patient contact.Results The SARS-CoV-2 prevalence in employees with daily patient contact, with 0% in the 1st phase and 7.4% in the 2nd phase, was not significantly higher than the prevalence in the control group with no patient contact (0.9% in the 1st phase, p = 0.4; and 8.6% in the 2nd phase, p = 0.8). Furthermore, physicians were not at a significantly higher risk of SARS-CoV-2 infection compared to technicians, nurses, or office staff.Conclusions This study shows that the abovementioned precaution measurements are effective in preventing transmission of SARS-CoV-2 infection in eye hospitals and enable us to resume practicing ophthalmology in a safe manner.
Keywords: conjunctiva; infectious diseases; microbiology